(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
In the contemporary landscape of global vocational education, the transition from traditional knowledge-transfer models to Competency-Based Education (CBE) has necessitated a fundamental re-evaluation of quality management systems. This article addresses the critical disparity between modern competency standards and archaic assessment mechanisms within vocational institutions. By analyzing the theoretical underpinnings of educational monitoring and the multidimensional nature of professional competencies, the study argues that traditional summative assessments are insufficient for gauging workforce readiness. Instead, a holistic, process-oriented monitoring system is proposed—one that integrates continuous feedback loops, authentic assessment strategies, and stakeholder engagement to ensure the employability of graduates. This foundational section explores the pedagogical imperatives for shifting towards a monitoring architecture that prioritizes the application of skills over the mere retention of knowledge.